Integral Waste Management in Primary Health Care centers: A Case Study in Mexico - Ocampo Escobedo, Rosa Llisel; Ortiz-Chacha, Christian S.; Risso Günther, Wanda María; Azamar Arismendi, Rosa Aurora (Horizonte Sanitario, 2021)
Objective: This paper aims to describe waste management in primary health care centers located in the municipality of Xalapa, Veracruz, Mexico, as a model case for developing countries. Material and methods: A observational, descriptive and cross-sectional study was conducted. The sample was made up of the seven primary healthcare centers located in the municipality of Xalapa, Veracruz, México. Data collection was carried out with a checklist designed according to the current legislation for the primary health care centers. Results: The global percentage of compliance was 55%, with variation between 47% and 63%. The stage of identification, separation and packaging recorded the highest percentage of compliance, while the temporary storage showed a lower percentage. Conclusion: The waste management in primary health care centers resulted in a level of compliance ranging from low to medium, which suggests the need for specific actions in order to improve waste management in health centers.